Consistency in size and asymmetry of the psoas major muscle among elite footballers. Issue 16 (26th May 2009) - Stewart, S; Stanton, W; Wilson, S; Hides, J
Abstract : Objective: To determine, using magnetic resonance imaging (MRI), the cross-sectional area (CSA) of the psoas major (PM) muscle across multiple vertebral levels, to examine any asymmetry of the PM muscle and investigate the consistency across vertebral levels, and to determine whether a relationship exists between low back pain (LBP) and the size or asymmetry of the PM muscle among elite Australian Rules football (AFL) players. Design: Observational cross-sectional study. Setting: Assessments and MRI examinations were carried out in a hospital setting. Participants: Thirty-one male elite AFL players aged between 20 and 32 years participated in the study. Risk Factors: The independent factors in the study were "asymmetry" (coded as ipsilateral or contralateral to kicking leg) and "group" (current LBP versus no current LBP). Main Outcome Measurements: The dependent variable in the study was the CSA of the PM muscle. Results: The PM muscle was larger on the side of the dominant kicking leg at all four vertebral levels measured (F = 7.28, p = 0.012). Participants who reported current LBP had larger PM muscles than the remainder of the players (F = 4.63, p = 0.041). Conclusion: Additional investigation into the underlying mechanisms of the observed differences in PM muscle size could help to develop treatment and rehabilitation programmes aimed at reducing the incidence of LBP among AFL players. Furthermore, asymmetry of the PM muscle was observed at multiple vertebral levels and therefore future studies may only need to take single-level measurements to assess for asymmetry.